Pendekatan Kimia Medisinal dalam Optimasi Senyawa Bioaktif dari Bahan Alam sebagai Kandidat Obat Antikanker - Saeful Amin; Neng Padia Amelia; Tiara Oktavia Ramadhan; Silvia Dwi Putri (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Cancer is one of the leading causes of death in the world, with the incidence rate continuing to increase every year. Conventional treatments such as chemotherapy and radiotherapy often have limitations, especially related to selectivity towards cancer cells and toxic side effects caused to normal cells. Therefore, an alternative approach that is more effective and safe is needed. One promising approach is the utilization of bioactive compounds from natural materials that are optimized through a medicinal chemistry approach. This study aims to examine the potential of natural compounds such as epigallocatechin gallate (EGCG) from green tea, berberine from Berberis vulgaris, curcumin from turmeric (Curcuma longa), and cardiotonic steroids (CTS) from Digitalis purpurea and Nerium oleander as anticancer agents, as well as their optimization strategies through structural modification, increased stability, and modern delivery technology. The method used is a systematic literature review of scientific articles from 2020 to 2025 obtained through the PubMed, ScienceDirect, and Google Scholar databases. The results of the study indicate that these compounds have various anticancer mechanisms of action, such as apoptosis induction, cell cycle inhibition, and activation of specific signaling pathways such as PI3K/Akt, MAPK, and ferroptosis. However, challenges such as low bioavailability, poor stability, and toxicity are still obstacles in their application. Through a medicinal chemistry approach, these compounds can be structurally modified or reformulated to improve their clinical effectiveness. In conclusion, the combination of natural wealth with medicinal chemistry innovation opens up great opportunities in the development of more selective, effective, and safe anticancer therapies in the future.